PooPatrol: ioT - Integrated dog litter identification and monitoring using machine learning. - Austria, John Marie E. Baligod, Roland carlos S. Erno, Gary Daniel I. Sandico, Pauline R. Sundiam. Ferdinand Francis R. 4 0 16; 5
u
Undergraduate Thesis : (Bachelor of Science in Computer Engineering) - Pamantasan ng Lungsod ng Maynila ,2024.
Keywords: 2 -- 0; 6; 20; 20; 2